High thermal conductivity driven by the unusual phonon relaxation time platform in 2D monolayer boron arsenide. Issue 42 (2nd July 2020) - Hu, Yanxiao; Li, Dengfeng; Yin, Yan; Li, Shichang; Zhou, Hangbo; Zhang, Gang
Abstract : The cubic boron arsenide (BAs) crystal has received extensive research attention because of its ultra-high thermal conductivity comparable to that of diamond. Abstract : The cubic boron arsenide (BAs) crystal has received extensive research attention because of its ultra-high thermal conductivity comparable to that of diamond. In this work, we performed a comprehensive study on the diffusive thermal properties of its two-dimensional (2D) counterpart, the monolayer honeycomb BAs (h-BAs), through solving the phonon Boltzmann transport equation combined with first-principles calculation. We found that unlike the pronounced contribution from out-of-plane acoustic phonons (ZA) in graphene, the high thermal conductivity (181 W m −1 K −1 at 300 K) of h-BAs is mainly contributed by in-plane phonon modes, instead of the ZA mode. This result is explained by the unique frequency-independent 'platform' region in the relaxation time of in-plane phonons. Moreover, we conducted a comparative study of thermal conductivity between 2D h-BAs and h-GaN, because both of them have a similar mass density. The thermal conductivity of h-BAs is one order of magnitude higher than that of h-GaN (16 W m −1 K −1 ), which is governed by the different phonon scattering process attributed to the opposite wavevector dependence in out-of-plane optical phonons. Our findings provide new insight into the physics of heat conduction in 2D materials, and demonstrate h-BAs to be a new thermally conductive 2D semiconductor.